Considerations for skin carcinogenesis experiments using inducible transgenic mouse models - Martyna C. Popis; Rebecca E. Wagner; Fernando Constantino-Casas; Sandra Blanco; Michaela Frye (BMC Research Notes, 2018)
Abstract Objective This study was designed to estimate the percentage of non-malignant skin tumours (papillomas) progressing to malignant squamous cell carcinomas (SCCs) in a carcinogenesis study using established transgenic mouse models. In our skin cancer model, we conditionally induced oncogenic point mutant alleles of p53 and k-ras in undifferentiated, basal cells of the epidermis. Results Upon activation of the transgenes through administration of tamoxifen, the vast majority of mice (> 80%) developed skin papillomas, yet primarily around the mouth. Since these tumours hindered the mice eating, they rapidly lost weight and needed to be culled before the papillomas progressed to SCCs. The mouth papillomas formed regardless of the route of application, including intraperitoneal injections, local application to the back skin, or subcutaneous insertion of a tamoxifen pellet. Implantation of a slow releasing tamoxifen pellet into 18 mice consistently led to papilloma formation, of which only one progressed to a malignant SCC. Thus, the challenges for skin carcinogenesis studies using this particular cancer mouse model are low conversion rates of papillomas to SCCs and high frequencies of mouth papilloma formation.